Treatment of Acute Diarrhea in Children Aged 1–5 Years Provided by Doctors in Surabaya - Athiyyah, Alpha Fardah; Irsan, Insyira Rayhana; Fatimah, Nurmawati (Folia Medica Indonesiana, 2023)
Highlights: 1. The focus of this study was on the treatment methods for acute diarrhea, which have not been extensively investigated in the region studied. 2. This study can provide an overview of doctors' adherence to the available guidelines for the treatment of acute diarrhea in children aged 1–5 years in Surabaya, Indonesia. Abstract: Diarrhea is the second leading cause of death among children under five, following pneumonia. Insufficient knowledge of diarrhea and dehydration management may contribute to this high mortality rate. Implementing prompt and effective management and prevention strategies has the potential to decrease morbidity and mortality associated with diarrhea. Therefore, this cross-sectional study aimed to investigate the treatment methods used by doctors for children aged 1–5 suffering from acute diarrhea in Surabaya, Indonesia. Data were collected from doctors in Surabaya using an online form containing case-based questions. Microsoft Excel for Mac version 16.17 (Microsoft Inc., Redmont, WA, USA) was used to process the binary data by calculating frequencies and percentages with a point estimate of 95% confidence interval (CI). A descriptive method was used in the data analysis, and the findings were presented in tables. From a total of 51 respondents who participated in this study, 18 (35.29%) only administered oral rehydration therapy. In addition, 49 respondents (96.08%) prescribed zinc supplementation for ten days, while 10 respondents (19.61%) opted for antibiotics. Interestingly, 49 respondents (96.08%) recommended both breast milk and food for the patients, and nearly all respondents provided guidance to the mother or caregiver of the patient. The findings of this study suggested that the respondents primarily used rehydration therapy to treat children suffering from acute diarrhea with moderate dehydration. However, some respondents still relied on antibiotics despite the available recommendations to use oral rehydration therapy. Nearly all respondents agreed on zinc supplementation, breast milk and food provision, and advice for the mother or caregiver of the patient. While certain aspects of the disease management for diarrhea align with the recommended guidelines, there is room for improvement in promoting the exclusive use of oral rehydration therapy and reducing unnecessary antibiotic prescriptions.